Electrochemical Activation and Its Prolonged Effect on the Durability of Bimetallic Pt-Based Electrocatalysts for PEMFCs - Angelina Pavlets; Ilya Pankov; Anastasia Alekseenko (Inorganics, 2023)
The present study, concerned with high-performance ORR catalysts, may be a valuable resource for a wide range of researchers within the fields of nanomaterials, electrocatalysis, and hydrogen energy. The objects of the research are electrocatalysts based on platinum–copper nanoparticles with onion-like and solid-solution structures. To evaluate the functional characteristics of the catalysts, the XRD, XRF, TEM, HAADF-STEM, and EDX methods, as well as the voltammetry method on a rotating disk electrode have been used. This work draws the attention of researchers to the significance of applying a protocol of electrochemically activating bimetallic catalysts in terms of the study of their functional characteristics on the rotating disk electrode. The choice of the potential range during the pre-cycling stage has been shown to play a crucial role in maintaining the durability of the catalysts. The activation of the PtCu/C catalyst during cycling of up to 1.0 V allows for an increase in the durability of the catalysts with onion-like and solid-solution structures of nanoparticles by 28% and 23%, respectively, as compared with activation of up to 1.2 V.